Near-fatal anaphylaxis with Kounis syndrome caused by Argas reflexus bite: a case report - Boni, Elisa (Clin Mol Allergy, 2020)
BACKGROUND: The pigeon tick Argas reflexus is a temporary parasite of pigeons. It bites during night hours and lies briefly on its prey, as long as it takes the blood meal. When pigeons are not accessible, ticks look for other hosts, invading nearby flats and biting humans. CASE PRESENTATION: We present the case of a woman aged 46 years who experienced severe anaphylaxis during the night which required emergency medical treatment, tracheal intubation and hospitalization in intensive care unit. Kounis syndrome was documented by transient ST depression and elevation of troponin. The allergological work up ruled out hypersensitivity to drugs, latex and foods containing alpha-gal, which is a cause of anaphylaxis. Basal serum tryptase was in normal range (8.63 ng/ml). When questioned about the presence of ticks, the patient brought into view various specimens of ticks that were recognized by an entomologist as Argas reflexus. CONCLUSIONS: An in vitro diagnosis of allergy to Argas reflexus is currently not feasible because, though the major allergen Arg r 1 has been isolated, allergen extracts are not commercially available. Therefore, the diagnosis of anaphylaxis from Argas reflexus, when other causes of anaphylaxis are excluded, must rely only on history and clinical findings, as well as on the presence of pigeons and/or pigeon ticks in the immediate domestic environment.